Conversion of Langmuir–Blodgett monolayers and bilayers of poly(amic acid) through polyimide to graphene. (7th December 2016) - Jo, Hye Jin; Lyu, Ji Hong; Ruoff, Rodney S; Lim, Hyunseob; Yoon, Seong In; Jeong, Hu Young; Shin, Tae Joo; Bielawski, Christopher W; Shin, Hyeon Suk
Abstract: Various solid carbon sources, particularly poly(methyl methacrylate), have been used as precursors to graphene. The corresponding growth process generally involves the decomposition of the solids to hydrocarbon gases followed by their adsorption on metallic substrates (e.g., Cu). We report a different approach that uses a thermally-resistant polyimide (PI) as a carbon precursor. Langmuir–Blodgett films of poly(amic acid) (PAA) were transferred to copper foils and then converted to graphene via a PI intermediate. The Cu foil substrate was also discovered to facilitate the orientation of aromatic moieties upon carbonization process of the PI. As approximately 50% of the initial quantity of the PAA was found to remain at 1000 °C, thermally-stable polymers may reduce the quantity of starting material required to prepare high quality films of graphene. Graphene grown using this method featured a relatively large domain size and an absence of adventitious adlayers.